Improving Students Affective Domain Through Asian Parliamentary Debate Technique - . Purwanto (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The objective of this research is to see the improvement of the students’ affective domain through Asian parliamentarydebate technique at English club of SMK Negeri 3 TerbanggiBesar Lampung Tengah. Affective Domain is related to the students’ motivation, value, attitude and behavior. Affective domain consists of some levels, receiving, responding, valuing, organization, characterization which also consists of some operational verbs in each level. Affective domain is one of the domains that should be improved during teaching and learning process. Observation, interview and questioners were used to collect the data. The researcher conducted observation for 3 times, interview for 2 times. The result of this study revealed that most operational verbs in each level were achieved during the Asian debate activity. However, at the level of characterization only some operational verbs were not well achieved based on the result of the questioners. Moreover, the student’s perception during interview was figured out that there was some improvement before and after the debate. Therefore, teachers are expected to implement the Asian debate technique to see the improvement of the students’ affective domain in learning English.